CPW Fed Hexagonal Patch Shape with Hexagonal slot Ultra Wideband Antenna - Gill, Suman; Ubhi, J S (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper hexagonal patch shape with hexagonal slot, ultra wideband antenna is proposed. The total dimensions of antenna are 55Ã—43.5mm. Sides of hexagonal patch are taken 13mm each and hexagonal slot sides are taken as 3mm each. The antenna resonates at two frequencies in ultra wideband range (UWB). There is enhancement in BW in upper range ultra wideband frequency from 6.2 GHz to 8.2GHz due to hexagonal slot cut in hexagonal patch. The design is carried out using Computer Simulation Technology (CST) Microwave Studio (MWS) suite. Co-Planar Waveguide (CPW) feed is used to feed antenna.